Poverty Alleviation of Micro-small Enterprises Recipients of Zakat through Financing of Zakat Organizer Institution in Makassar - Muhammad Saleh Mire (Budapest International Research and Critics University, 2021)
This study aimed to explain the factors that affect the ability to pay zakat for micro and small entrepreneurs who receive zakat funds from BMT, a type of zakat organization. This study focuses on how to improve the status of recipients of zakat funds, meaning that Mustahiq (recipients) will become Muzakki (payers), so this study only discusses productive zakat. The results of the study using logistic regression showed that religiosity, capital, business knowledge, education, length of business, customer duration, paying zakat had a significant and simultaneous effect on the ability to pay zakat. Separately, the duration of business has the greatest effect on the dependent variable, while the payment of sedekah has no effect. Furthermore, it was found that Mustahik had not been able to change his status to Muzakki through the provision of capital funds from BMT. This fact is supported by the results of the previous regression analysis.